The effect of stance width on the electromyographical activity of eight superficial thigh muscles during back squat with different bar loads - Paoli, A.; Marcolin, G.; Petrone, N. (The Journal of Strength and Conditioning Research, 2009)
Many strength trainers believe that varying the stance width during the back squat can target specific muscles of the thigh. The aim of the present work was to test this theory measuring the activation of 8 thigh muscles while performing back squats at 3 stance widths and with 3 different bar loads. Six experienced lifters performed 3 sets of 10 repetitions of squats, each one with a different stance width, using 3 resistances: no load, 30% of 1-repetition maximum (1RM), and 70% 1RM. Sets were separated by 6 minutes of rest. Electromyographic (EMG) surface electrodes were placed on the vastus medialis, vastus lateralis, rectus femoris, semitendinosus, biceps femoris, gluteus maximus, gluteus medium, and adductor maior. Analysis of variance and Scheffè post hoc tests indicated a significant difference in EMG activity only for the gluteus maximus; in particular, there was a higher electrical activity of this muscle when back squats were performed at the maximum stance widths at 0 and 70% 1RM. There were no significant differences concerning the EMG activity of the other analyzed muscles. These findings suggest that a large width is necessary for a greater activation of the gluteus maximus during back squats.